Evaluation of the efficacy of Dummaladi lepa in the management of Vipadika - Abegunasekara, N.S.; Jayakody, J.A.D.P.P. (2nd International Conference on Ayurveda, Unani, Siddha and Traditional medicine(2nd ICAUST), 2014)
"Vipadika" is horrible itching, paining, dry skin disease which is occurred in feet. This research was considered about the effect of an herbal cream that can be used for Vipadika. 30 patients were randomly selected on the basis of the inclusion criteria from dermatology clinic at the outside patient unit of Gampaha Wickramarachchi Ayurvedic teaching hospital. Al1 the patients were randomly divided into two equal groups as Group A and Group B. Both groups were given the selected ayurveda modalities as intemal medicine. In addition to group A was given "Dummaladi lepa" as an external application.Assessment was done through observation of signs and symptoms before and after the treatment. The follow up period was 21 days. Pain, Fissuring, Itching and Eruptions were recorded throughout the follow up period. They were taken to the account for the evaluation and severity of the symptoms were rated using five point scales.The results indicate that Group A has shown a significant decline of severity on pain, flssuring, itching and eruptions after three weeks. According to the analysis all the P values of the Group A in the comparison of before and after three weeks were less than 0.05.The study revealed that Dummaladi lepa is an effective herbal cream for Vipadika.
Keywords: Vipadika; dummaladi lepa